Internal Communication Analysis at Bank BJB Syariah KC Bogor - Muhammad Kafin Abda'u; Puji Wahono; Terrylina Arvinta Monoarfa, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research was conducted at Bank BJB Syariah KC Bogor. The aim of this research is to find out a picture of the company's internal communication in order to design an internal communication strategy to minimize the communication barriers faced. The population of this study were employees of Bank BJB Syariah KC Bogor and 4 samples were taken as informants. The analysis of this research was prepared using a descriptive approach to provide a comprehensive picture of this research. Data for this research was obtained through observation, interviews, documentation and literature study methods. Triangulation technique is used as a data validity technique. The analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of research regarding internal communication at Bank BJB Syariah KC Bogor include: 1) The internal communication structure is based on the organizational hierarchy structure, namely vertical and horizontal and in its application uses direct channels, direct action and digital media. 2) Obstacles faced include lack of information transparency, late information distribution, and miscommunication. 3) Strategies to overcome obstacles, namely providing open discussion spaces, communication training, and effective application of digital media. 4) The key factors for the success of internal communication are management's commitment to opening effective communication channels, sophisticated digital communication media, and the practice of implementing the organization's work culture values. The advice given is from the agency. The suggestion given is to hold internal communication training for employees to maintain or improve their communication skills.